Juridical Analysis of The Validity of Interreligious Marriages Based on MK Ruling No. 24/PUU‐XX/2022 - Budi Prasetyo Adi Wibowo; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this study is to find out whether interfaith marriages are legal based on Constitutional Court Decision No.24/PUU‐XX/2022 and to identify the legal implications of court decisions on interfaith marriages. The problem discussed in this study is how legal interfaith marriages are based on the Marriage Law No. 1 of 1974 and what are the legal consequences for court decisions regarding interfaith marriages. Normative legal studies are used in this study. The data sources used are the main data sources that are relevant to the research author's problem, namely the Constitutional Court Decision Number 24/PUUXX/ 2022, Decree Number 9 of 1975, Law Number 23 of 2006 concerning Population Administration and secondary data sources in the form of books ‐books, journals, internet related to research topics. The results of the study show that interfaith marriages are clearly invalid or it can be concluded based on Article 2 of the Marriage Law No. 1 of 1974 which states that legal marriages must be carried out according to all religions and beliefs. That is, marriage can only be interpreted if the couple (prospective husband and wife) adheres to the same religion. And the legal value of the decision of the interfaith marriage court has been examined based on Article 35 letter a of Law Number 23 of 2006 concerning Population Administration and in the case of marriage based on an interfaith court decision, it is permissible to establish a marriage based on a court decision.